Stereoselective Synthesis of Benzo[a]quinolizidines via Aerobic DDQ-Catalyzed Allylation and Reductive Cyclization - Jung, Sunhwa; Yoon, Seungri; Lee, Jae Kyun; Min, Sun-Joon (ACS Publications, 2022)
Stereoselective synthesis of C-4-substituted benzo[a]-quinolizidines via redox-controlled catalytic C-C-bond-forming reactions was carried out. Aerobic DDQ-catalyzed allylation of N-Cbz tetrahydroisoquinolines efficiently provided alpha-allylated products 5, which were transformed to enones 6 via cross-metathesis reactions using the second-generation Hoveyda-Grubbs catalyst. Palladium-catalyzed hydrogenation of 6 prompted alkene reduction, protecting group removal, and intramolecular reductive amination in one step to afford the desired benzo[a]quinolizidines 7 as single diastereomers.